PERANCANGAN SISTEM MONITORING SUHU, KELEMBABAN DAN KONSENTRASI GAS AMONIA PADA KANDANG AYAM PEDAGING - Valentino Ode Anugrah Kristanto; Adharul Muttaqin; Muhammad Aswin (Jurnal Mahasiswa TEUB, 2022)
The condition of the broiler cage during the rearing period can affect the quality of the chicken meat produced. Conditions in the cage that are not comfortable for chickens can cause disease and inhibit the growth of chickens. One of the main factors that can affect the condition of the chicken coop is the temperature and humidity of the air. A comfortable temperature for chickens is between 19oC to 33oC, and humidity is between 30%RH to 70%RH. In addition, the air in the chicken coop is also susceptible to being polluted by ammonia gas produced from chicken manure. Ammonia gas with concentrations exceeding 25ppm for more than 8 hours can harm the health of chickens and breeders. The purpose of this study was to design a system that can monitor conditions in the chicken coop in the form of temperature, humidity, and ammonia gas concentration. The system uses a NodeMCU ESP8266 microcontroller, a DHT11 temperature and humidity sensor, and an MQ-135 gas sensor. The system made can measure temperature and humidity, with an average error of 1.97% for temperature, and 3.55% for humidity. Meanwhile, the results of the measurement of ammonia gas concentration have approached the characteristics in the datasheet. The stored measurement data is visualized on the ThingSpeak web application. In addition, the system can also send warning messages via the Telegram application when the measurement value is abnormal or there is a sudden change in value.Keywords: Broiler, temperature, humidity, ammonia gas